Education and Training of Information Users: An overview - Rajagopalan, T. S. (Journal of Information and Knowledge, 1978)
Mentions the need, purpose, objectives, and factors for consideration in user education programmes. Discusses the characteristics of different categories of users and the levels of user education. Presents an organisational structure for user education programmes in India. Suggests that the national information policy for information user education and mentions the factors that are to be covered by such a policy.